Behavioural and endocrine impact of artificial selection for winning in the siamese fighting fish - Ramos, Andreia Maria Cerejo; Gonçalves, David (University of Saint Joseph, 2021)
Aggression clearly has an adaptive value as it is necessary to secure resources for survival, growth, and reproduction. The Siamese fighting fish, Betta splendens, have endured a prolonged process of artificial selection for winning paired-fight contests across Southeast Asia, resulting in strains of short-fin aggressive “fighters”. Across centuries, Thai breeders have been selecting these strains by discarding loser batches and allowing winner batches to breed, claiming that they are significantly more aggressive than wild-types. This natural experiment provides a powerful context to investigate the biological basis of aggressive behaviour in fish, the topic of this thesis. To study aggression, it is important to validate and standardize behavioural assays appropriate for the species under study. Further, different aggression-eliciting stimuli, such as live opponents, 3D models, video playback, or mirror images, may elicit non-equivalent behavioural and physiological responses. For B. splendens, in particular, quantifying aggression from live fights is not ethically acceptable as the high levels of aggression of this species usually result in injuries or even death of the opponent. In Chapter II, it was shown that mirror images elicit very similar aggressive displays and endocrine responses to an interacting opponent behind a transparent partition, validating the use of this test to measure aggression in this model species. Further, it was shown that circulating levels of both androgens (11-ketotestosterone and testosterone) and corticosteroids (cortisol) increased in response to the aggression challenge, even in the absence of conflict resolution, questioning the role of these hormones during present and future aggressive contests. Using the previously validated mirror assay and also tests with live conspecifics, we assessed the impact of selection for winning by comparing, in Chapter III, male and female aggressive behaviour of lab-raised fighter and wild-type strains. The hypothesis that selection for male winners enhanced aggressive displays was confirmed, suggesting that the duration and frequency of threat and attack behaviour correlates with winning probability. However, females of the fighter strain, which are not selected for fights, were also more aggressive than wild-type females. This suggests that male and female aggression share common genetic pathways and physiological mechanisms and raises the possibility that selection for alleles that favour male aggression may have promoted intersexual genetic conflict in this species. After confirming the expected differences in aggressive behaviour between fighter and wild-type fish, the following question was whether endocrine systems, in particular those previously shown to respond to aggression, could have been targeted by the selection process. From previous studies in fish and other vertebrates, it was hypothesised that selection for winners could have increased constitutive levels of androgens or led to an enhanced androgen response to a social challenge. However, in chapter IV, it was shown that levels of 11-ketotestosterone and its response to aggression was similar in males of both strains, questioning the role of androgens in the modulation of aggression in B. splendens. On the contrary, constitutive levels of cortisol and the response of this hormone to an aggression challenge were higher in wild-type compared with fighter fish, supporting previous findings that associated high aggression with a blunted cortisol response. Overall, results from Chapter IV suggest that selection for winning had a stronger impact on the hypothalamus-pituitary-interrenal axis than in the hypothalamus-pituitary-gonadal axis. My results support the assumption of the “Challenge Hypothesis” proposed by John Wingfield and collaborators in 1990 to explain the relationship between androgens and aggression, according to which androgen levels above a reproductive baseline are a consequence of the frequency and intensity of social interactions, in particular of male-male agonistic encounters. It is becoming clear that androgens increase rapidly after an aggressive contest, independently of fight outcome. However, the function of this increase remains unclear as the frequency of aggressive displays was unrelated with post-fight androgen levels and constitutive levels of androgens, and androgen responsiveness, were similar between fighter and wild-type males. Results obtained for cortisol agree with a “corticosteroid-mediated dominance hypothesis” whereby low baseline levels and a blunted response of corticosteroids would be associated with a dominant status and high aggression. The work advances our knowledge about the endocrine regulation of aggressive behaviour in B. splendens and opens several testable hypotheses about the role of androgens and corticosteroids in the regulation of fish aggressive behaviour
Keywords: Thesis and Dissertations PhD in Science (D-SC); University of Saint Joseph

SURVIVAL, MORPHOLOGY AND REPRODUCTION OF ENHALUS ACOROIDES (L.f.) ROYLE IN THE BOLINAO-ANDA REEF SYSTEM, NW PHILIPPINES: EFFECTS OF VARYING LIGHT CONDITIONS - Tagulao, Karen Araño (University of Saint Joseph, 2023)
Seagrasses play a critical role in coastal ecosystems worldwide, providing various ecosystem services based on their region and genus. In Southeast Asia, where seagrass biodiversity and extents are at their highest, the livelihoods and food security of many coastal communities depend on these plants. Despite their ecological and economic importance, seagrasses face global threats from human activities such as pollution and land use changes. Enhalus acoroides, a widely distributed seagrass species in the tropical Indo-Pacific region, is particularly valuable for coastal management and conservation efforts due to its size and provision of various ecosystem services. Although previous research has indicated that it is less sensitive to environmental changes than other tropical seagrass species, recent reports highlight its vulnerability to siltation and eutrophication. This dissertation aimed to examine how Enhalus responds and adapts to changes in light availability, taking into account both morphological adaptation and phenotypic plasticity. Field surveys, reciprocal transplantation field experiments, and investigations of sexual reproductive effort were conducted in the Bolinao-Anda Reef system (NW Philippines) to evaluate the impact of long-term environmental changes on Enhalus populations. The findings of this study revealed that Enhalus has the capacity to adapt its traits and survive changes in depth, light gradients, and different habitat types. This is evidenced by larger shoots in low-light environments, which is apparently a response to the reduction in light availability, as evidenced in both in situ and experimental setups. Larger leaf surface area in light-reduced setups also had higher concentration of chlorophylls a and b pigments. Transplants from light-reduced environments, although morphologically large, appeared more vulnerable (with low survival values) to environmental changes associated with translocation. Being morphologically large is therefore likely a stress response to light reduction, allocating more energy on light harvesting than sexual reproduction. Reciprocal transplantation experiments indicated a high survival rate, suggesting the potential of Enhalus for use in rehabilitation. However, despite having wider plasticity to adapt to light-limitation, they can be wiped out when threshold is reached. This thesis underscores the need for further research on Enhalus' response to stressors, genetic variation, and adaptive capacity to address conservation and management challenges
Keywords: Enhalus acoroides; Thesis and Dissertations PhD in Science (D-SC); University of Saint Joseph; light availability; phenotypic plasticity; seagrass; transplantation

ISOLATION AND CHARACTERISATION OF PLASTIC POLYETHYLENE TEREPHTHALATE (PET) DEGRADING AND POLYHYDROXYALKANOATES (PHAs) PRODUCING BACTERIA FROM SOIL AND WATER - Saidu, Muhammad Bashir (University of Saint Joseph, 2023)
The demand for plastic has led to enormous plastic waste in the environment, which persist and negatively impact the ecosystems. Polyethylene terephthalate (PET) is one of the most common thermoplastic polymers available on the market. The concerns about plastic waste generated an interest in strategies to enhance its biodegradation and finding alternative polymers. In this work was investigated the possibility of using bacteria to degrade PET and to produce bioplastics (Polyhydroxyalkanoates, PHAs). Finally, the integration of the two processes was tested. Overall, the work aimed to investigate the potential to recycle PET into bioplastic using bacteria. The potential of bacterial consortia from various environmental samples to degrade PET granules in liquid matrix was investigated. . The results revealed maximum PET granules degradation of 1.1 % by one of the tested consortia. PET degradation intermediate terephthalic acid (TPA) was not detected at the end of 55 days. Fourier-transform infrared spectroscopy (FTIR) results showed major spectral peak shifts and bends on PET chemical structure compared to non-inoculated control. The biodegradation of PET films buried in the soil (A), with mangrove plants (B), and bioaugmented with a bacterial consortium (C) was also investigated. The experiments were conducted for 270 days at ambient conditions. The results revealed no difference between treatments in the degradation, with a maximum weight loss of 0.118 % in the bioaugmented treatment. Nevertheless, Scanning Electron Microscope (SEM) and FTIR results indicated significant surface changes, spectral peak shifts, and stretches in PET chemical structures. Bacterial consortia isolated from the soil of the experimental treatments were assessed for degradation of PET monomers, TPA and monoethylene glycol (MEG), and intermediate Bis(2-hydroxyethyl) terephthalate (BHET). The consortia were inoculated in flasks containing minimal media with 1000 mg/L TPA or BHET or1113 mg/L MEG as the sole carbon source. Results showed complete degradation of TPA and significant degradation of BHET (96.09%), and MEG (83.65%) by the consortia. In the second part of the study, bacteria were isolated from various environmental samples and screened for PHA production using Sudan Black B staining on colonies and smeared glass slides. Transmission Electron Microscope images were captured to confirm the intracellular PHA inclusions. A total of 35 isolates were screened for PHA, and 22 showed positive staining. The isolate showing higher levels of PHA synthesis (EC2-30-3) was identified based on 16S rRNA gene sequence as Bacillus sp. and selected for PET monomers degradation and fermentation cultures for PHA production. It was cultured in minimal (Moreira et al., 2013) media with 1000 mg/L TPA and 1113 mg/L MEG as the carbon source for eight days. The isolate grew better in media containing MEG, which was selected as a substrate model for PHA fermentation. To integrate PET monomers biodegradation and production of PHA, the isolate was cultured in 0.2 % MEG. A control with 0.2 % of glucose was prepared, and the cultures were incubated for 96 hours. Bacillus sp. EC2-30-3 showed higher PHA accumulation in media supplied with MEG (40.31%) than glucose (25.53%). This is the first report showing that Bacillus sp. uses PET monomer as carbon source to produce a biopolymer. FTIR results of the extracted PHA identified its functional units as C–H, CH3, C=O, and C–O groups. The absorption bands obtained are closely related to the structure of PHB. The study thus confirmed the ability of the isolated bacteria to degrade PET monomers and produce biopolymers. The results of this work open the possibility for upscaling the use of bacteria to mitigate the impact of PET on the environment while producing environmentally friendly bioplastics
Keywords: Biodiversity; China; Green Roof; Macao SAR; Nature-based Solutions; Sustainability; Thesis and Dissertations PhD in Science (D-SC); University of Saint Joseph